1997
DOI: 10.1016/s0042-6989(97)00050-3
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin elevates the c-wave of the electroretinogram of the rabbit eye by increasing the transepithelial potential

Abstract: The influence of serotonin (5-hydroxytryptamine, 5-HT) and serotonin analogues on the direct current electroretinogram (d.c. ERG) and the standing potential of the albino rabbit eye (SP) was studied. After unilateral vitrectomy, corneal recordings were obtained during simultaneous intravitreal perfusion with a control solution alternating with 5-HT at concentrations of 25, 120 and 200 microM. The c-wave increased at 25 and 120 microM when changing from control solution to test solution (P < 0.05) but did not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 38 publications
2
0
0
Order By: Relevance
“…It appears that endogenous serotonin has inhibitory role on the b-wave generating mechanisms in pigeon retina, but excitatory role on the same mechanisms in rabbit retina. It has been found that application of exogenous serotonin increases the amplitude of the b-wave in cat (Skrandies and Wässle 1988) and rabbit (Bragadottir et al 1997) retina, which supports the suggestion that serotoninergic system has excitatory role on the b-wave generating mechanism in mammalian retina. Our finding that serotonin increas-es the amplitude of the b-wave in frog retina indicates that serotoninergic system has similar role in the amphibian retina as well.…”
Section: Discussionsupporting
confidence: 71%
“…It appears that endogenous serotonin has inhibitory role on the b-wave generating mechanisms in pigeon retina, but excitatory role on the same mechanisms in rabbit retina. It has been found that application of exogenous serotonin increases the amplitude of the b-wave in cat (Skrandies and Wässle 1988) and rabbit (Bragadottir et al 1997) retina, which supports the suggestion that serotoninergic system has excitatory role on the b-wave generating mechanism in mammalian retina. Our finding that serotonin increas-es the amplitude of the b-wave in frog retina indicates that serotoninergic system has similar role in the amphibian retina as well.…”
Section: Discussionsupporting
confidence: 71%
“…As these potentials can be related to specific cellular events, they provide information about RPE function and how that may be altered by disease or experimental manipulation [68]. In our study, we found significant preservation of c-wave ERG, and that could be correlated with strong RPE junctional integrity and healthy RPE [69,70]. Previously, using this model, we have seen that supplementation of daily zeaxanthin improved c-wave response compared to untreated mice [29].…”
Section: Discussionsupporting
confidence: 71%